Affective mechanisms linking role ambiguity to employee turnover - Junça Silva, A.; Rodrigues, R. (International Journal of Organizational Analysis, 2024)
Purpose: This study relied on the job demands and resource model to understand employees’ turnover intentions. Recent studies have consistently lent support for the significant association between role ambiguity and turnover intentions; however, only a handful of studies focused on examining the potential mediators in this association. We argued that role ambiguity positively influences turnover intentions through affective mechanisms: job involvement and satisfaction. Design/Methodology/approach: To test the model, a large sample of working adults participated (N = 505). Findings: Structural equation modeling results showed that role ambiguity, job involvement, and job satisfaction were significantly associated with turnover intentions. Moreover, a serial mediation was found among the variables: employees with low levels of role ambiguity tended to report higher job involvement, which further increased their satisfaction with the job and subsequently decreased their turnover intentions. Research limitations/implications: the cross-sectional design is a limitation. Practical implications: Practical suggestions regarding how organizations can reduce employee turnover are discussed. Originality/value: The findings provide support for theory-driven interventions to address developing the intention to stay at work among working adults.